2011
DOI: 10.1007/s11340-011-9564-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Seawater and Low Temperatures on Polymeric Foam Core Material

Abstract: Polymeric composite sandwich structures, often manufactured using a thick foam core material and thin composite facings, are of significant interest in naval applications. This paper summarizes the coupled effect of sea water and low temperature on the mechanical properties of closed cell polymeric H100 foam core material. The study considers the effects of harsh sea environmental conditions on the fracture and deformation behavior of such a foam material under complex loading conditions that include tension, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 17 publications
(44 reference statements)
0
18
0
Order By: Relevance
“…Additional studies [11][12][13] have also indicated that polymer foams' mechanical properties are substantially affected by moisture absorption. Several researchers [14][15][16] investigated the mechanical degradation of foam-cored sandwich structures exposed to varying hygrothermal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies [11][12][13] have also indicated that polymer foams' mechanical properties are substantially affected by moisture absorption. Several researchers [14][15][16] investigated the mechanical degradation of foam-cored sandwich structures exposed to varying hygrothermal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, the flexural and interfacial fracture properties of PVC foam cored sandwich structures have been studied to some extent [25][26][27] with the experimental results presenting how the toughness of the core-face sheet interface is reduced at humid environments. Siriruk et al [28] have also studied the effect of sea water and low temperature on PVC foam material. They noted that the tensile modulus and strength were degraded by moisture but no significant difference was seen when the moisture was combined with low temperature.…”
Section: Hygrothermal Effects On Pmi Foam and Its Sandwich Structuresmentioning
confidence: 99%
“…Water sorption and the different properties of these two materials could lead to debonding when the sandwich composites are exposed to fluid ingression. Siriruk et al showed that the interfacial fracture toughness of the sandwich structure decreased by 30% due to the combined sea water ingression and low temperature. The loss of interfacial fracture toughness could lead to debonding of the core/skin interface and cause irreversible failures in sandwich composite structures.…”
Section: Introductionmentioning
confidence: 99%
“…The typical approach of those studies is to individually investigate the diffusion process in each constituent, that is, FRP sheet and polymeric foam core, of the sandwich composites. Siriruk et al conducted experiments to measure water uptake in polymeric PVC foam core, and reported variations of weight gain due to different geometries of the foam samples. Earl and Shenoi investigated the absorption behavior of closed‐cell PVC foam cores, and reported a multistage absorption process.…”
Section: Introductionmentioning
confidence: 99%